A note on influence of subgroup restrictions in finite group structure - R. Khazal; N. P. Mukherjee (International Journal of Mathematics and Mathematical Sciences)
The structure of a finite group under specific restrictions respectively on its maximal, minimal and prime power subgroups has been investigated in this paper.